UNILATERAL DISTALIZATION OF MAXILLARY MOLAR BY PENDULUM APPLIANCE - Safra Mauna; Maria Purbiati (Faculty of Dentistry, Universitas Indonesia, 2006)
Pendulum appliance is one of intraoral appliances to distalize molars for correction of class II molar relationship or space gaining in the maxillary arch. Its major advantages are: no need to depend on patient compliance; ease of fabrication; and better patient acceptance. In this case, 22 years old female patient with class II division 2 malocclusion was treated with pendulum appliance for unilateral distalization of the maxillary molar teeth. Pendulum can distalize second molar until 4 mm in 4 months and continues to distalize first molar in 3 months. Nevertheless, relapse 2 mm happens during anterior retraction. This case has shown that pendulum is an effective and reliable appliance for distalizing maxillary molars. However, molar distalization is at the expense of moderate anchorage loss during anterior retraction, which could possibly be reduced if the anchor unit is adequately reinforced.